Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1973
DOI: 10.1139/g73-063
|View full text |Cite
|
Sign up to set email alerts
|

CYTOGENETIC, ECOLOGIC AND MORPHOLOGIC STUDIES IN BRAZILIAN FORMS OF PASPALUM NOTATUM

Abstract: The somatic number, meiotic behavior, morphology and ecology of five forms of Paspalum notatum are reported. All of them showed a chromosome number of 2n = 40. There is a fair degree of variation in the frequencies of meiotic chromosome configurations in different strains of a given form, but for four of the five we could characterize them as showing about 2-3 IV and 14-16 II. The type Capivari presents distinct differences in relation to all others, with about 1 IV and 18 II. The prevalence of I and III is ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The low efficiency of meiotic sacs to produce progenies through sexual events may also be ascribed to meiotic irregularities that have been observed by several authors in different tetraploid strains of P. notatum (Magoon and Manchanda 1961, Fernandes et al 1973, Stein et al 2004. Cytologically unbalanced male and female gametes may lead to pre-or post-zygotic abortion.…”
Section: ⎯⎯⎯⎯mentioning
confidence: 96%
“…The low efficiency of meiotic sacs to produce progenies through sexual events may also be ascribed to meiotic irregularities that have been observed by several authors in different tetraploid strains of P. notatum (Magoon and Manchanda 1961, Fernandes et al 1973, Stein et al 2004. Cytologically unbalanced male and female gametes may lead to pre-or post-zygotic abortion.…”
Section: ⎯⎯⎯⎯mentioning
confidence: 96%
“…On the other hand, the meiotic irregularities in natural apomictic polyploid species are numerous and well-documented for a number of genera, as for example Paspalum (Moraes-Fernandes et al 1968, 1973, 1974, Pagliarini et al 2001, Adamovski et al 2005, Dahmer et al 2008. In these species, a regularization of the meiotic behavior would not be essential for species propagation and success, as the embryo is formed by apomixis, provided that, in the pseudogamous species, there is some fertile pollen to ensure endosperm formation.…”
Section: Resultsmentioning
confidence: 99%
“…Studies reported pollen viability of ecotypes and of native apomictic accessions of P. notatum in the state of Rio Grande do Sul: Dahmer et al (2008) found pollen viability ranging from 81.0 to 91.47% in the ecotype "Bagual", and of 86.0 to 98.0% in the ecotype "André da Rocha". Moraes-Fernandes et al (1973) reported pollen fertility ranging from 0 to 84.3%; and Reis et al (2008) found pollen viability ranging from 88.99 to 95.06% in 53 accessions, despite the numerous meiotic irregularities found. The high pollen viability of apomictic plants is expected, since seed formation occurs only if there is fertilization of the polar nuclei of the embryo sac by one of the gametic nuclei of pollen grain, due to pseudogamy, typical in species of Paspalum and Brachiaria, which present this mode of reproduction (Pagliarini and Pozzobon 2004).…”
Section: Analyses Of Pollen Viabilitymentioning
confidence: 99%